Technology for the Visual Inspection of Aircraft Surfaces Using Programmable Unmanned Aerial Vehicles - Blokhinov, Yu. B.; Gorbachev, V. A.; Nikitin, A. D.; Skryabin, S. V. (Journal of computer & systems sciences international, 2019)
The technology for the visual inspection of aircraft surfaces using programmable unmanned aerial vehicles (drones) is presented. When developing the technology, special attention is paid to the problem of the drone’s indoor navigation where the signal from satellite positioning systems is weak or there is no signal, as well as to the development of algorithmic programs and software for detecting both the drone and damage to the aircraft surface based on video analysis. The results of testing the technology in enclosed spaces under conditions close to the expected operating conditions are given.